Homogenous Dispersion And Interfacial Bonding Of Carbon Nanotube Reinforced With Aluminum Matrix Composite: A Review - Hashim, Hanizam; Salleh, Mohd Shukor; Omar, Mohd Zaidi (De Gruyter, 2019)
Recent developments in the field of carbon nanotube (CNT) have attracted attentions on a new development of aluminum matrix composite (AMC). Homogenous dispersion and interfacial bonding of CNT/metal matrix are the two main problems yet to have sound solutions.In general, to ensure uniform dispersion, the overall process can be divided into three steps: preprocessing, mixing and post processing. This paper summarizes previousworks on solid and liquid processing techniques which some are more successful than others by looking at the improvement of the composite tensile strengths. On the other hand the interfacial bonding depends on the existance of Al4C3 phase and physical conditions of CNT. Both elements must be controlled for the optimized results. The review presented here would be used as references in the future works to fabricate higher strength CNT/aluminum composites